Effects of Acetic Acid and Different Salt Concentrations on the Shelf Life of Caviar from Rainbow Trout (Oncorhynchus mykiss W. 1792) - Inanli, Ayse Gurel; Oksuztepe, Gulsum; Ozpolat, Emine; Coban, Ozlem Emir (Medwell Online, 2011)
In this study, the intention is the investigation of the chemical, microbiological and sensorial changes occurring during cold storage (4 +/- 1 degrees C) of the caviar obtained from rainbow trout (Oncorhynchus mykiss, W. 1792) that is wet salted and added acetic acid in different ratios. If data obtained as results of this study, an effect on microbiological and chemical parameters of samples were observed depending on increasing acetic acid and salt ratios. In addition, it was determined any effect of acetic acid on the organoleptic of samples. In this study especially when the sensorial data were evaluated the shelf-life of the groups were determined as 14 days in 5% salt containing A and B groups as 21 days in 10% salt containing C and D groups.
Keywords: Caviar; rainbow trout; shelf-life; salt; acetic acid; chemical; microbiological; sensorial